Peran Keluarga sebagai Gereja Rumah Tangga dalam Membangun Karakter Anak di Era Digital - Yanti Vidarosa Naibaho; Nova Florentina Ambarwati; Reflina Sinaga; Ester Julinda Simarmata; Liana; Fiber Yun Almanda Ginting (Yayasan Pustaka Karya Mandiri, 2026)
The digital communication era has fundamentally transformed patterns of relationship, authority, and the space of faith formation within the Catholic family, demanding a renewed affirmation of the family's role as Ecclesia Domestica (the Domestic Church) in building children's character. This study aims to analyze how families fulfil their function as the domestic church in shaping children's character amid the currents of digital communication, and to formulate relevant pastoral strategies to strengthen that function. The study employs a descriptive qualitative approach through library research on six recent scholarly articles concerning the family, faith education, and the digital era, analyzed thematically to identify patterns, relationships, and conceptual novelty. The findings show that the family carries out three principal roles as the domestic church: educator/teacher of faith, sanctifying priest through family prayer and liturgy, and guiding shepherd who instils moral values and responsibility. The formation of children's character in the digital era is strongly influenced by parental example, the intensity of open and empathetic communication, parents' spiritual-digital literacy, and the consistency of shared prayer and Scripture reading enriched by the wise use of digital media. The study further finds that challenges such as parental busyness, low digital literacy, and limited spiritual accompaniment can be addressed through a collaborative pastoral model involving families, the local parish/church, and digital communities. This study recommends strengthening spiritual digital-literacy programmes for parents and digital-based family catechetical modules as concrete steps to reaffirm the family as the primary space for shaping children's character.